A Numerical Failure Analysis of Multi-bolted Joints in FRP Laminates Based on Basalt Fibers. (2015) - Nerilli, Francesca; Marino, Michele; Vairo, Giuseppe
Abstract: This paper aims to model the progressive damage of multi-bolted joints connecting structural elements made up of FRP (fiber- reinforced polymers) composite laminates and comprising different fiber materials (namely, based on basalt, carbon and glass), as well as different stacking sequences. Differences in failure mode and ultimate-load values are numerically investigated. A numerical home-made finite element model has been conceived, implemented, and validated by means of available experimental data. The numerical model is based on an incremental displacement-based approach and on a plane-stress bi-dimensional for- mulation. The stress analysis has been performed by accounting for micro-structural stress-strain localization mechanisms, and describing the progressive damage process by implementing a failure criterion operating at the constituents' scale (namely, the Huang's criterion). Proposed results have highlighted that bolted joints based on basalt-FRP laminates and defined by a double- bolted configuration exhibited bearing failure loads comparable to those computed for glass-FRP and carbon-FRP laminates. In the case of single-bolted joints, the use of carbon-FRP laminates allowed to obtain the best mechanical properties, although joints based on basalt-FRP laminates numerically-experienced mechanical response and strength features always comparable with those of glass-FRP.